Examination of Canned Meat Products in Forensic Commodity Analysis - M. A. Zubova (Теория и практика судебной экспертизы, 2021)
The article presents a speciﬁc methodology for forensic commodity examination of food products: expert analysis of canned meat and meat-containing products made of diﬀerent raw materials. On a speciﬁc example from expert practice – conduct of a forensic commodity examination of a consignment of 12600 cans of meat product “beef stew” – the author shows the research program and its stages: sampling, establishment of the commodity aﬃliation of goods, analysis of the actual characteristics (markings, consumer packaging) of the tested products and veriﬁcation of their compliance with the requirements of regulatory and technical documentation; measurement of quantitative indicators of products; examination of the submitted laboratory tests protocols.